2012
DOI: 10.1007/s00417-012-2136-z
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year review of assault-related open-globe injuries at an urban hospital

Abstract: Assault-related OGIs carry an extremely poor visual prognosis and a high rate of enucleations. Only eighteen eyes (12.2 %) recovered VA ≥ 20/40. We found initial VA of NLP and zone 3 injury to be significant predictors of final VA of NLP or undergoing enucleation. Penetrating injuries were less likely to have a final VA of NLP or an enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
6
21
1
Order By: Relevance
“…4,16-23 Regarding studies examining risk factors for RD, three reports previously identified anatomic zone as being predictive of RD. 22,24,25 Two other studies from Iran and Germany studied risk of RD after open globe trauma using multiple clinical variables, but their small cohort sizes, 116 and 52 open globe injuries respectively, limit the accuracy of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…4,16-23 Regarding studies examining risk factors for RD, three reports previously identified anatomic zone as being predictive of RD. 22,24,25 Two other studies from Iran and Germany studied risk of RD after open globe trauma using multiple clinical variables, but their small cohort sizes, 116 and 52 open globe injuries respectively, limit the accuracy of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Stryjewski, C.M. 8 Although assault-related open-globe injuries have been shown to be more severe with worse presenting VA, the 39.9% incidence rate was not substantially higher than another large study that included open-globe injuries from all causes; Schmidt and colleagues published a series of 214 open-globe patients, of whom 34.1% presented with retinal detachment. 34 The vast majority of open-globe studies have included the presence or absence of retinal detachment at the time of initial presentation, but few have evaluated the incidence afterwards, and even fewer have described the timing of detachment when it does occur.…”
Section: Incidence and Timing Of Retinal Detachment In Open-globe Injurymentioning
confidence: 97%
“…[5][6][7][8][9][10][11][12][13][14][15][16] Many studies have demonstrated that retinal detachment both at the time of initial presentation and in the postoperative course after open-globe repair is associated with poor vision, phthisis, and enucleation. 1 Defined as any fullthickness wound of the eye wall, open-globe injuries can result in significant damage to the anterior and posterior segments of the eye and necessitate multiple surgical interventions over the course of years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was 10.1% in 118 cases of open eye injuries in southern Israel from 1996 to 2005 44 . According to the 2001–2010 report by the Trauma Center, at University Hospital, Newark, New Jersey, 6.0% of 183 work-related injured eyes underwent enucleation, 45 and 45.9% of 148 assault-related injured eyes with NLP and 31.1% received enucleation 46 . According to the 2001–2012 report of the Trauma Center in Queens, New York, there were 441 cases of eye injuries, with the enucleation rate of 5.0% 47 .…”
Section: Comprehensive Development Of Medical Treatment For Eye Injurmentioning
confidence: 99%